Pengaruh Pembiayaan Murâbahah Dan Mudhârabah Terhadap Kesejahteraan Nasabah (Studi Kasus Pada Bank Syariah Indonesia KCP BSD Tangerang Selatan) - Aam Ridwan; Umi Khusnul Khotimah; Hidayat (Ma'had Aly PP. Zainul Hasan Genggong, 2024)
At this time there are not a few banks that carry out activities conventionally or based on sharia principles. Currently the development of the Islamic financial market (Financial Market Sharia) is rife in the world, especially in countries with a majority Muslim population. This was marked by the establishment of the Islamic Financial Market in Kuala Lumpur which was pioneered by Islamic countries. The progress of the Sharia Financial Market in Indonesia, especially in Islamic banking and insurance is quite significant, followed by the Islamic capital market and pawnshops. Many financing contracts are carried out in the practice of Islamic financial institutions, for example murabahah, mudharabah, ijarah, musyarakah and so on. In this thesis the authors focus on murabaha and mudharabah financing.The design used in this study is a correlational analysis design (a problem to find a relationship between two phenomena) precisely causal correlation. Data collection uses research instruments, data analysis is quantitative/statistical. The primary data used in this study are 132 customers who received financing according to the criteria and the secondary data in this study are in the form of documents and archives at Bank Syariah Indonesia which contain reports on customer funds that carry out murabaha and mudharabah financing. The sampling technique in this study used purposive sampling, which is a method of determining respondents to be sampled based on certain criteria. Based on the results of data analysis with the help of the SPSS 26.0 program, research that has been conducted at Bank Syariah Indonesia KCP BSD Tangerang using linear regression analysis through SPSS program data processing shows that, (1) There is an effect of Murabahah financing on the welfare of customers of Bank Syariah Indonesia KCP BSD Tangerang. The statistical test results showed that Fcount = 27,898 at db 1 and 94 was 3.94 at the 5% level. Based on the explanation above, 27,898 > 3.94 at the 5% level, so H0 is rejected, meaning that there is an influence of Murabahah financing on customer welfare of Mandiri Syariah Bank KCP Tangerang, (2) There is an influence of Mudharabah financing on the welfare of customers of Bank Syariah Indonesia KCP BSD Tangerang. The statistical test results showed that Fcount = 15.048 at db 1 and 34 was 4.13 at the 5% leve